Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Guimaraes, Aretha Franklin; de Alagao Querido, Luciano Carramaschi; Rocha, Taina; de Jesus Rodrigues, Domingos; Viana, Pedro Lage; de Godoy Bergallo, Helena; Fernandes, Geraldo Wilson; Toma, Tiago Shizen Pacheco; Streit, Helena; Overbeck, Gerhard Ernst; de Souza, Alberico Queiroz Salgueiro; Lima, Albertina Pimentel; et al. (Elsevier, 2024)
The lack of synthesized information regarding biodiversity is a major problem among researchers, leading to a pervasive cycle where ecologists make field campaigns to collect information that already exists and yet has not been made available for a broader audience. This problem leads to long-lasting effects in public policies such as spending money multiple times to conduct similar studies in the same area. We aim to identify this knowledge gap by synthesizing information available regarding two Brazilian long-term biodiversity programs and the metadata generated by them. Using a unique dataset containing 1904 metadata, we identified patterns of metadata distribution and intensity of research conducted in Brazil, as well as where we should concentrate research efforts in the next decades. We found that the majority of metadata were about vertebrates, followed by plants, invertebrates, and fungi. Caatinga was the biome with least metadata, and that there's still a lack of information regarding all biomes in Brazil, with none of them being sufficiently sampled. We hope that these results will have implications for broader conservation and management guiding, as well as to funding allocation programs.
Keywords: Biodiversity monitoring; Brazilian biodiversity; Data-deficiency in Brazil; Research gaps; Tropical forests; Wallacean shortfall